AN EXPLORATION OF HOW TECHNOLOGY USE INFLUENCES RELATIONAL ETHIC SCORES OF EMERGING ADULT ROMANTIC RELATIONSHIPS - Epps, Courtney (East Carolina University, 2016)
Technology is virtually used within all facets of life such as in employment locations, educational institutions, and in interpersonal relationships and has become a necessary tool of contemporary living. Technology is useful for connecting and accomplishing tasks and much research has concentrated on the benefits of technology for fulfilling these functions. It is also known that technology use is highest among emerging adults, ages 18-25. Little research has been done to determine the influence of technology use on romantic relationships, especially among the emerging adult population. Knowing the impact of technology use on romantic relationships is crucial for mental health clinicians since technology is now integrated into everyday living. The research questions addressed in this study were aimed at shedding light on the impact of technology use on romantic relationships in the emerging adult population. These research questions were grounded in contextual family therapy used by mental health clinicians to assess and treat clients who present for therapy. The research questions explored in this study were: 1) Does a participant's perception of the impact of technology use (i.e. very positive, somewhat positive, somewhat negative, very negative) on their relationship influence relational ethics trust scores and intimacy scores in committed relationships? 2) Is there a difference in these relational ethics scores based on Facebook use between cohabiting couples versus non-cohabiting couples? 3) How does a participant's perception of the impact of technology use on their relationship impact relationship satisfaction and relational ethics scores? Data came from a collegiate sample in the Southeastern United States consisting of 248 respondents involved in any type of romantic relationship. Results indicated that a negative perception of the impact of technology use on a respondent's relationship was associated with lower relational outcomes for relational ethics, trust, intimacy, and relationship satisfaction. Results also indicated that there was no difference in relational ethic scores based on Facebook use between cohabiting verses non-cohabiting couples; however, Facebook use alone did impact relational ethics scores. Therefore, technology use can be described as negatively impacting various relational outcomes. Implications and future directions for mental health clinicians and researchers are discussed.
Keywords: Technology Use; Relational Ethics; Contextual Family Therapy; Emerging Adults; Technology--Moral and ethical aspects; Technology and youth; Technology--Social aspects; Interpersonal relations